A general equation for the polarization curves of proton exchange membrane fuel cell under hydrogen crossover current measurement - Tang, F.; Tang, Z.; Yang, Y.; Li, B.; Zhang, C.; Ming, P.
Hydrogen crossover in proton exchange membrane fuel cells (PEMFCs)is an effective indicator for evaluating the health condition of PEMFCs. Electrochemical measurement is an indirect but convenient method for assessing the hydrogen crossover; nevertheless, the meaning of the characteristics from the measured signals is not consensus to lack quantitative method. In this paper, we have developed a general expression to quantify the relationship among the measured signals by decomposing the electrochemical processes inside the PEMFCs when measuring the hydrogen crossover current. The theoretical polarization curves were derived from the general equation and confirmed by the experiments on a 25 cm2 single cell. This work clarifies the intrinsic relevancies among these electrochemical methods and would help develop a new evaluation methodology for PEMFCs.
Keywords: HYDROGEN CROSSOVER; PEMFC; POLARIZATION CURVE; PSM; GCM